Avaliação da saúde bucal na atenção básica: a perspectiva do usuário - Soares, Samara Carollyne Mafra (2007)
Nowadays, the basic attention in health works according to the Health Family Program (HFP), which is responsible for the organization of the health services with view to provide an appropriate attendance to the needs of the population. Its expansion is expressive in whole country and, the oral health, included in this process, has been seen as a possibility of change the health practices centered in the disease. In face of this perspective, the proposal of study is to discover possible changes in the health care model of oral health in a district, made possible through the perception, evaluation and degree of satisfaction of the user s health service. To reach such objectives, the district of Macaíba in the State of Rio Grande do Norte, was chosen for operational subjects, such as time of implantation of HFP and great covering of this program. The current research used interviews structured with objectives and subjectives questions and questionnaires of socioeconomic characterization addressed to two hundred and seventy (270) individuals (ninety users of an Urban PSF, ninety of a Rural PSF and ninety of an unit non PSF). The analysis of the data was accomplished through the software SPSS/99, that made possible a statistical and analytic appreciation. The HFP units and non HFP units has shown to sort the common odontology problems of the community, and this didn't establish a direct relationship with the general satisfaction. On the other hands, the programmed consultation is related with lager satisfaction of the users. The access form to the odontology treatment of the Units, the satisfaction with the attendance rendered by the dentist and the equip, enough dentists for the community and the social class of the user were decisive for the general satisfaction with the service of oral health. On the other hand, variables as age and education, resolution of the problem and physical conditions of the unit didn't influence the general satisfaction. In spite of the progresses in the implantation of the oral health in ESF, preventive activities, visits at home, access and social participation still reproduce the traditional model of attendance, showing a primary change process